Measure Levels of Social Conformity, Self-Regulation, and Self-Identity Development Among Students - Alma Vorfi Lama; Ahmad Zarkasyi; Ramil Abbasov; Zohaib Hassan Sain (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The increase in juvenile delinquency by 10.7% between 2021 and 2024 indicates a serious problem in the psychosocial development of the younger generation. This phenomenon is influenced not only by individual factors but also by increasingly complex social environmental pressures. This study aims to measure levels of social conformity, self-management, and identity formation among students of the Faculty of Tarbiyah at the Miftahul Ulum Islamic Institute in Lumajang in the 2024–2025 academic year. The research focuses on obtaining empirical evidence regarding students’ tendencies in social behavior and self-regulation when facing academic and social environmental demands. A descriptive quantitative method was employed using a five-point Likert-scale questionnaire. The study involved 96 respondents selected through snowball sampling techniques. Data analysis was conducted using SPSS version 21.0, with descriptive statistics, particularly mean scores, to represent the central tendency of each research variable. The results indicate that students’ levels of social conformity range from moderate to high, particularly in aspects related to opinion adjustment and concerns about social acceptance. Meanwhile, students’ self-management abilities and identity formation are categorized as good, with the highest mean scores found in the dimensions of self-understanding and identity commitment. These findings underscore the importance of strengthening character education programs, counseling services, and the development of self-management skills within higher education institutions. Such efforts are expected to reduce deviant behavior while fostering students’ personal, social, and moral maturity.